EFEKTIVITAS MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS VII SMP NEGERI 9 BENGKULU TENGAH - Eci Ningsih; Reni Kusmiarti (Universitas Hamzanwadi, 2026)
The purpose of this study was to improve the descriptive text writing skills of seventh grade students of SMP Negeri 9 Bengkulu Tengah using picture media. The low ability of students in developing ideas, describing objects, and composing coherent texts became the basis for conducting this study. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research subjects consisted of 26 seventh grade students selected through a total sampling technique. Data were obtained through descriptive text writing tests at the pretest and posttest stages. Data analysis techniques used included descriptive statistics to describe student learning outcomes, the Shapiro-Wilk normality test to test data distribution, a paired t-test to determine differences in results before and after treatment, and N-Gain calculations to measure the level of improvement in students' overall abilities. The results showed that the average score increased from 67.96 in the pretest to 80.50 in the posttest, with a percentage increase of 18.47%. The results of the paired test showed a significance value <0.001, which means there was a significant difference between before and after the use of picture media. Furthermore, the N-Gain value of 0.39 is in the moderate category. The implications of this study indicate that images can be used as an effective learning medium to improve descriptive text writing skills because they can help students develop ideas, understand objects concretely, and compose texts in a more structured manner in Indonesian language learning.